Effect of Substituent on The Oxidation of Some Heterocyclic Semicarbazones by Quinolinium Fluorochromate - Vimala, T.; Jani Bai, T.S. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of 2,6-diphenylpiperidin-4-one semicarbazone and some 3-alkyl substituted- 2,6-diphenylpiperidin-4-one semicarbazones by quinolinium flucrochromate have been studied in aqueous acetic acid medium. The reactions are catalyzed by acid, the acid catalyzed reactions being very fast, precluded determination of their order in acid medium. The effect of added sodium sulphate and the influence of dielectric strength together indicate the reaction to be an ion-dipole type. The stoichiometry is 1:1 and the product of oxidation is the corresponding ketone. Activation energies and related thermodynamic parameters have been calculated. A suitable mechanism and hence a corresponding rate equation has been derived. The reaction is subjected to steric hindrance by the alkyl substituent.